Parasites and Contaminants in Breeding Eider Ducks, Nunavut - Gilchrist, Grant; Provencher, Jennifer (Polar Data Catalogue, 2017)
Each year several thousand pairs of eiders nest on the island and are caught by researchers using mist-nets as they arrive at the colony each spring. In 2013 and 2014 female eiders were caught at the East Bay and given an oral dose of PANACUR (known anti-parasite treatment widely used in animal husbandry) or a placebo treatment of water. A small blood sample was also taken to assess female blood mercury levels. All females were then marked using standard nasal tags, making them identifiable from observation blinds throughout the rest of the season. Observers monitored nesting females for date egg laying, size of clutch, date of hatch, and number of successful ducklings. Analysis are currently underway. The experimental group will then be compared to untreated (parasite infected) females for productivity through the above nesting metrics. In addition to the above experimental manipulation, the blood sample taken when female eiders arrived at the colony was also used to assess mercury and lead burdens of the females in relation to immunoglobulin (IgY) and hormone (corticosterone) levels. Contaminant burdens are compared between years, and how they vary in terms of female eider arrival timing and condition. Analysis is currently under way.